Exploration of Antimicrobial Potency of Mangrove Symbiont Against Multi-Drug Resistant Bacteria - Delianis Pringgenies; Wilis Ari Setyati; Ali Djunaedi; Rini Pramesti; Siti Rudiyanti; Dafit Ariyanto (Jurnal Ilmiah Perikanan dan Kelautan, 2021)
Highlight ResearchAntimicrobial potential against the test microbesRhizhopora mucronata isolate showed 95% homology with Bacillus subtilis, and 97% homology with Bacillus oceanisediminis,Acanthus ilicifolius isolate showed 96% homology with Paracoccus caeni, and 89% homology with Bacillus circulans. The study found 4 isolates with antimicrobial potency against MDR pathogenic microbes.The symbiont microbes taken from Rhizophora mucronata and Acanthus ilicifolius were determined to be of the genus Bacillus and Paracoccus AbstractAntimicrobial property of mangrove symbiont have the ability to fight Multi Drug Resistant bacteria which were Staphylococcus aureus, Escherichia coli, and Vibrio haryeyi. This study aimed to determine the potential of symbiont microbes from the root of Rhizopora mucronata and Acanthus iilicifolius as antimicrobial agents against multi-drug resistant (MDR) pathogenic microbes. This research was conducted during July to November 2020. The MDR bacteria were S. aureus, E. coli, and V. harveyi MDR test microbes. The symbiont microbes were identified through molecular analyses (PCR 16S rDNA). Isolation of symbiont microbes from R. mucronata resulted in 16 isolates, while isolation from A. iilicifolius resulted in 14 isolates. Based on the antimicrobial qualitative test against S. aureus, 8 out of 16 microbial isolates from R. mucronata were found to show antimicrobial properties. The testing of A. ilicifolius symbiont microbes against S. aureus showed 8 out of 14 isolates with antimicrobial properties. The test against E. coli resulted in 2 out of 16 microbial isolates from R. mucronata and 5 out of 14 isolates from A. ilicifolius with antimicrobial properties. The test against V. harveyi resulted in two out of 16 microbial isolates from R.mucronata and 4 out of 14 isolates from A. ilicifolius with antimicrobial properties. The quantitative test found 2 isolates from R. mucronta, namely isolates RM10 and RM12, with antimicrobial properties against MDR strain E. coli, with the best isolate being RM10, which produced 11.22 mm of inhibition zone diameter. Furthermore, the selection of isolates was based on the size of the inhibition zone, the clearness of the inhibition zone and the potential for antibacterial activity. Based on their overall antimicrobial potential against the test microbes, four isolates were selected.  Molecular analyses of RM12 isolate showed 95% homology with Bacillus subtilis, of RM 10 isolate showed 97% homology with Bacillus oceanisediminis, of AC isolate showed 96% homology with Paracoccus caeni, and of AC 5 isolate showed 89% homology with Bacillus circulans. The study found four isolates with antimicrobial potency against MDR pathogenic microbes. The symbiont microbes taken from R. mucronata and A. ilicifolius were determined to be of the genus Bacillus and Paracoccus.